Upfc Compensated Transmission Line Fault Location Based on Travelling Wave Theory and Wavelet Modulus Maxima - Prasad, K. Durga Syam; Sravanthi, K.; Babu, Dr. Ch. Sai (International Journal of Engineering and Technology, 2018)
Location of fault in a transmission line which includes flexible AC transmission system (FACTS) devices is a difficult task. This paper comprises of unified power flow controller (UPFC). The implementation control technique for UPFC devices set up dynamic problems in power system that must be reflecting on issues related to power system protection. The occurrence of a fault in the fault loop containing a UPFC affects transient and steady-state parameters of voltage and current in the power system. In this paper the identification of fault section before or after UPFC for a transmission line with wavelet fuzzy logic system discriminator. Wavelet technique extracts features, and the faulty location is found when the normalized features are fed to the fuzzy logic system. As soon as the fault section is located, the control shifts to that and is analyzed basing on the representation of the traveling wave theory through wavelet modulus maxima. This criterion detects the faulty section with respect to FACTS device very accuratelyin terms of distance from relay point. The above-said method is simulated for various fault situations and locations with wide changes in the conditions of operation in the presence of UPFC.